Evaluasi dan Perbaikan User Interface Situs Web PT Asia Civil Indonesia dengan Metode System Usability Scale dan Design Thinking - Jeysen Immanuel Wenas; Fatwa Ramdani; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Company profile is an image of the professionalism of a company that can be used as an effective marketing tool because there are visual elements in the form of images and text The PT Asia Civil Indonesia website is an Indonesian company website that provides consulting, project management & construction and delivery services for various 'Capital Projects' including infrastructure, property, industrial, marine, energy and commodity assets However, it was found that in fact there were several problems that occurred on the PT Asia Civil Indonesia website, namely the first regarding the content design which is currently still felt to be monotonous and the second is regarding the distribution of information, it is felt that users are still have long loading This research was conducted with the aim of generating solution ideas that can support solving problems experienced by users when accessing the PT Asia Civil Indonesia website Design Thinking is a problem solving method that focuses on the user or the user, then for the testing phase using usability testing with the System Usability Scale approach Tests carried out using the System Usability Scale approach got a score of 80 with an adjective ratings rating that was above â€œGoodâ€ and below â€œExcellentâ€ and had increased to grade â€œBâ€ and Acceptability Ranges in the Acceptable category From these results, respondents successfully completed several tasks given and it is known that the user interface of the PT Asia Civil Indonesia website is included in the acceptable value range with a good adjective rating and Acceptable